2016
DOI: 10.1007/s00431-016-2758-y
|View full text |Cite
|
Sign up to set email alerts
|

Neurally adjusted ventilatory assist (NAVA) in preterm newborn infants with respiratory distress syndrome—a randomized controlled trial

Abstract: • NAVA improves patient-ventilator synchrony during invasive ventilation. • Lower airway pressures and oxygen requirements are achieved with NAVA during invasive ventilation in preterm infants by comparison with conventional ventilation. What is new: • Infants suffering from PPHN did not tolerate NAVA in the acute phase of their illness. • The traditional extubation criteria relying on inspiratory pressures and spontaneous breathing efforts were not clinically applicable during NAVA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 30 publications
1
55
0
1
Order By: Relevance
“…There was no significant difference in the primary outcome of the duration of ventilation (35 versus 26 h, p = 0.21). There was also no difference in the incidence of BPD, but the study was not powered to detect this [15].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…There was no significant difference in the primary outcome of the duration of ventilation (35 versus 26 h, p = 0.21). There was also no difference in the incidence of BPD, but the study was not powered to detect this [15].…”
Section: Discussionmentioning
confidence: 94%
“…The results of short-term studies [5][6][7][8][9][10][11][12][13][14][15] suggest that both PAV and NAVA improved oxygenation and were associated with lower airway pressures compared to conventional or other triggered modes of ventilation in prematurely born infants with evolving BPD, otherwise known as chronic pulmonary insufficiency of prematurity (CPIP) [16]. There are no studies in that population comparing PAV and NAVA, and hence the aim of this study was to compare the effect of PAV and NAVA on the oxygenation index in infants with evolving or established BPD.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies examined the very short-term effects of NAVA. Some reported improved patient-ventilator interaction, or decreased PIP within 24 h of NAVA use (10,14). Oda et al reported NAVA use in 14 extremely low birth weight infants.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive NAVA has been used in neonates, and studies have shown that it is a safe and feasible mode of synchronized ventilation, improves patient‐ventilator interaction, provides lower PIP and may improve patient comfort . NIV‐NAVA is a relatively new ventilatory strategy .…”
Section: Discussionmentioning
confidence: 99%